Investment, Energy Consumption and CO2 Emissions: An Analysis on the Strategy of Industry Development - Hong, Cheng-Yih; Huang, Chung-Huang; Li, Jian-Fa (International Journal of Energy Economics and Policy, 2017)
This study employs a Dynamic Environmental Industry-related Model to estimate the economic spillover effect and the CO2 emissions from both R&D of government and private equipment investment. We classify the industries into four subgroups which are the high economic effect with high emission coefficient, low economic effect with high emission coefficient, low economic effect with low emission coefficient and high economic effect with low emission coefficient. The present study attempts to measure the CO2 emission of both governmental R&D and private equipment investment, and further to propose the direction of Taiwan’s industrial development. Keywords: Investment, CO2 Emission Coefficient, Dynamic Environmental Industry-related Model JEL Classifications: C6, Q50, Q58